Selectivity and its future transformations in building design systems (Journal of the College of Basic Education, 2022)
The research focused on selectivity and future transformations in the construction of design systems, focusing on the use of theoretical frameworks and theories, theoretical models with the effective effect of the designer and the recipient of the choice among them, and providing a greater number of options in line with the requirements of the user life. The first chapter included the problem of the research represented by the following question: What are the mechanisms of achieving selectivity in the variables of design systems for industrial products?The objective of the research was to identify mechanisms of selectivity in the variables of design systems for industrial products. The limits of this research included electrical appliances products for Electrolux and LG manufactured in 2016 - 2017. The second chapter contains the axes of the theoretical framework. The third chapter covered the research procedures of the study society. While the fourth chapter contains the findings and conclusions reached by the researcher and the most important of these results as follows:- Intelligent techniques in the formation of a functional performance system through functional enrichment through the interaction of aesthetic shape, which is based on the various mechanisms that are not pre-traded in the demonstration and the use of the technological changes and changes by means and methods developed in all models because of their clear impact on user selectivity Within his new era.The most important conclusions in the research:- The mechanism of the correlation between the recipient and the product is achieved through the relationship of the formal harmony and the implications that are employed in the product on the basis of the clear cognitive structures of the recipient by the transformation of the data of the intellectual structures in the design and the creation of new mechanisms that contribute to the selectivity of the physical and moral integrity of the achievements. And direct contact with the user and imposed by the behavior of psychologically influential in the process of usage.